Influence of geometric conditions on the heat transfer of a multilayer wire-on-tube condenser (Revista Cientifica Ingenio Magno, 2021)
In this paper, a theoretical simulation of the influence of geometric parameters of a multilayer wire-on-tube condenser by forced convection, on the thermal capacity is presented. The geometric parameters under study are the wire diameter, the number of wires and wire pitch. The simulation was performed for two domestic refrigerators with the same type of condenser, but using the refrigerants R134a and R600a. Different empirical correlations were also analyzed for the convective heat transfer coefficient, thus selecting the one that best adjusted to previous experimental data, in this case the Zhukauskas correlation. According to the results obtained, the number of wires and their diameter are the factors that most affect heat transfer, increasing heat dissipation in the condenser between 4% and 6%. Finally, the wire pitch had a lesser influence on heat transfer.
Keywords: condenser; domestic refrigerator; heat transfer; convective coefficient